Desa Inklusif: Strategi Mewujudkan Kesejahteraan Kelompok Rentan - Putri, Suci Ramadhani; Mahfuz, M.; Nizamudin, Nizamudin (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2024)
This article aims to explain strategies for empowering vulnerable groups through Inclusive Villages. This article is library research with research sources originating from primary and secondary data. The primary data source for this article is literature related to Inclusive Villages in Indonesia and Vulnerable Groups. The secondary sources are literature that can support this article, such as relevant Islamic literature. Some groups have unique and distinctive forms of diversity, so they need more access to basic services. This group is referred to as a vulnerable group. A prosperous Muslim community, especially vulnerable groups, is part of a form of implementing inclusive Islamic values. Through value ukhuwah Islamiyah, musawah and ihsan Apart from that, it is also an effort to gain prosperity and avoid disaster, because by improving the economic welfare of vulnerable groups, we are also maintaining the values of society. Maqashid Sharia. The strategic efforts undertaken can be classified into internal efforts and external efforts. Internal efforts are to build awareness of vulnerable groups to get involved and voice their interests through village deliberation media (musdes). The external effort is to ensure that regulations and policies set by the Government protect the rights of vulnerable groups. Apart from that, it is also important to carry out socialization efforts involving all elements and society.